Note a margine del D.P.R. 23 agosto 2019 n. 131: le nuove disposizioni in materia di donazioni di cellule riproduttive a cinque anni dalla Corte cost. n. 162/2014 (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
With the D.P.R. no. 131/2019 Italy implemented the directive on reproductive cell donation. Five years after the decision of the Constitutional court, which stated the constitutional illegitimacy of the prohibition of heterologous fecundation as regulated by the law no. 40/2004, the legislative void has been filled.The new D.P.R. highlights the differences between the discipline of homologous artificial fertilization and heterologous fertilisation with donation from third parties, in open contrast with what the Constitutional court stated in 2014. The author analyses the D.P.R. and the problematic aspects of informed consent in the new discipline.
Keywords: Medically assisted reproduction; reproductive cell donation; economical implications of RCD; heterologous fertilisation